MARKETING STRATEGY OF GOLD SAVING PRODUCTS IN ISLAMIC PAWNSHOP - Asrandi, Muh; Masse, Rahman Ambo; Wahab, Abdul (Khatulistiwa, 2024)
Gold Savings is a service for buying and selling gold at affordable prices through custodial facilities. This gold savings product was launched aim of helping people who want to buy gold with minimal capital. This study aims to clarify the implementation of the marketing strategy for gold savings products and the barriers to marketing gold savings products at the Islamic pawnshop Sidrap Branch. In this study, the authors used a qualitative methods field research approach. Data acquisition techniques used are observation, interviews, and documentation. The results of this study indicate that the marketing strategy of gold deposit products carried out by Islamic pawnshop Sidrap Branch is based on the marketing mix strategy, while Pegadaian Syariah Sidrap Branch focuses on the promotion mix. Focus on other marketing mix strategies. Promotional mix strategies include advertising, personal selling, promotion, and public relations. There are two constraints regarding marketing gold savings products. Mostly, it is a factor that comes from the customer, and the Islamic pawnshop's side lacks understanding of the gold savings product itself as it is a place without quality products. Readers not only know about investment products such as gold savings but also have some technical knowledge that is still lacking, but the technology currently being developed makes it easier for customers to find the information they ordered.